2020
DOI: 10.1007/s42991-020-00093-z
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of the wolf (Canis lupus) in a near-natural ecosystem in Mongolia

Abstract: The increasing animosity towards wolves (Canislupus) by livestock-keeping nomads in Mongolia and the accompanying conflicts highlight the urgent need for knowledge about the feeding behavior of wolves, since information on the feeding ecology of wolves in Mongolia is rare, especially in the mountain taiga and mountain forest steppe regions of Northern Mongolia. Those regions are characterized by a relatively high wildlife diversity and are sparsely populated by humans. To face this problem, 137 wolf scats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 41 publications
(98 reference statements)
1
2
0
1
Order By: Relevance
“…Our most parsimonious model included terrain landscapes such as ruggedness, slope and pastureland, which were negatively associated with wolf attacks, and suggested that higher elevation was related with more livestock killings. This finding is in accordance with previous work, which found wolves select for mountainous terrain over flat steppes in Mongolia and some flat terrain also used by livestock for grazing (Tiralla et al, 2021), as also in Pakistan (Kabir et al, 2017). Since predators chase the prey, landscape topography becomes a significant factor for carnivore habitat use and distribution (Hua et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Our most parsimonious model included terrain landscapes such as ruggedness, slope and pastureland, which were negatively associated with wolf attacks, and suggested that higher elevation was related with more livestock killings. This finding is in accordance with previous work, which found wolves select for mountainous terrain over flat steppes in Mongolia and some flat terrain also used by livestock for grazing (Tiralla et al, 2021), as also in Pakistan (Kabir et al, 2017). Since predators chase the prey, landscape topography becomes a significant factor for carnivore habitat use and distribution (Hua et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…25% forest cover within home ranges; Linnell et al 2021), likely also enabled by the low anthropogenic influences in these regions. Similarly, other large carnivores commonly associated with forest habitats can persist in savannas and steppes provided sufficient protection and low levels of human disturbance, such as wolves in Central Asian steppes or North American prairies (Riley et al 2004;Tiralla et al 2021), but these habitats have often been the confidence intervals and partial residuals for low, medium, and high levels of forest cover (10th, 50th and 90th percentile in our dataset) are highlighted in different colors. Other variables are kept at their mean values for computing marginal effects first to lose large carnivores once human pressure increased (Laliberte and Ripple 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The constantly increased availability of invertebrate biomass on the market has resulted in an enlarged number of commercial foods. It should be highlighted that the ancestors of domestic dogs and cats ingest invertebrates as a part of their natural diets ( Behrendorff et al., 2016 ; Tiralla et al., 2021 ; Woolley et al., 2020 ). Thus, the implementation of “novel” insect ingredients is in fact back to nature.…”
Section: Insects In Petfoodmentioning
confidence: 99%